KEANEKARAGAMAN JENIS BURUNG PADA HUTAN DATARAN RENDAH DI KOMPLEKS GUNUNG BULUSARAUNG TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Risma Illa Maulany; Jumriah Lira; Amran Achmad; Nida' Sari Achmad (Forestry Faculty of Universitas Hasanuddin, 2019)
Lowland Forest at the complex of Bulusaraung mountain in the Bantimurung Bulusaraung National Park is one of important habitat of birds in South Sulawesi. This study aimed to identify bird’s diversity in the Lowland Forest of Bantimurung Bulusaraung National Park for ecotourism purposes. This research was carried out for 2 months between April and May 2018. The data were gathered by using line transect method. The data were analyzed by using Shannon-Weiner diversity index, Evenness index, Margalef species richness index, and Sorensen Similarity index. The result of the study showed that, there were 23 species of birds found in the three lines of observation tracks. There were 19 species found in Balleanging, 12 species in Kattokaddaro and 15 species found in Tompobulu.The highest value of bird diversity index was found in Tompobulu (H '= 1,73) followed by Balleanging (H' = 1,54) and Kattokaddaro routes (H '= 1,43). Therefore, the diversity of bird species in the three observation pathways can be used as objects and attractions in the development of ecotourism based on bird watching in wildlife conservation efforts.